2017
DOI: 10.4103/jispcd.jispcd_146_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessing prevalence of temporomandibular disorders among university students: A questionnaire study

Abstract: Aim:The aim of this study is to assess the prevalence of temporomandibular disorders (TMDs) among university students.Objectives:The etiology of TMD is of multifactorial, and our study is designed to assess the prevalence of TMD in an institution within a university. Various parameters including trauma, malocclusion, stress assessment - its correlation with the timing, the duration of TMD in meeting the deadlines, and examinations have been assessed.Materials and Methods:A standard questionnaire-based study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
10
17
1
Order By: Relevance
“…Similar to the role of psychological factors in the development of TMD, test anxiety is assumed to increase the risk of TMD in health sciences students [ 26 ]. This data supporting the association between test anxiety and TMD can be of great importance for the prevention and management of these conditions particularly in health professions students who are more prone to develop TMD than other students [ 25 ]. However, the association through the application of Fonseca's questionnaire and Test Anxiety Inventory should be further investigated.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar to the role of psychological factors in the development of TMD, test anxiety is assumed to increase the risk of TMD in health sciences students [ 26 ]. This data supporting the association between test anxiety and TMD can be of great importance for the prevention and management of these conditions particularly in health professions students who are more prone to develop TMD than other students [ 25 ]. However, the association through the application of Fonseca's questionnaire and Test Anxiety Inventory should be further investigated.…”
Section: Discussionsupporting
confidence: 54%
“…TMD was observed in 42.9% of university students in Taiwan [ 23 ], and 30.6% of medical and dental students demonstrated TMD in Nepal [ 24 ]. However, in India, 22.6% of university students reported the symptoms of TMD [ 25 ]. These variations in the prevalence estimates can be related to racial differences, demographic factors in each study, and diversity in study methodology [ 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was carried out in SPSS 14.0. The T-test was used to analyze the difference in the continuous variables between the two groups, and the chi-square test was used to evaluate clinical categorical measures (23,24). The Pearson correlation coefficient was used to calculate the correlations between age and identified metabolites in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…This concluded that age, as a factor, was not signi icant in the prevalence of TMJ disorder. Karthick et al also found the same signi icant indings (Ha ila et al, 2017). In contrast, Menghelli et al and Bertoli et al showed students in older age signi icantly were prevalent of developing TMDs (de Paiva Bertoli et al, 2018;Minghelli et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
“…Modi et al reported 159 subjects of 21-22 years were the most affected with TMD as compared to other 97 subjects who were below 20 years (Modi et al, 2012). A previous study among undiagnosed undergraduate students demonstrated a higher prevalence of TMD in students of 22-23 years (Ha ila et al, 2017). The prevalence of TMD can affect any individual of any age group, with a higher proportion seen in women aged 20-45 years (Minghelli et al, 2014).…”
Section: Resultsmentioning
confidence: 90%